RANCANG BANGUN APLIKASI E-SERTIFIKAT BERBASIS WEB MENGGUNAKAN METODE PENGEMBANGAN WATERFALL - Agariadne Dwinggo Samala; Bayu Ramadhani Fajri (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2020)
Certification is a determination given by a professional organization to someone to show that the person has competence, is able to do a specific job or task. Quality Assurance and Learning Development Institute Universitas Negeri Padang (LP3M UNP) currently still issues paper-based certificates manually for each training activity. Issuance of certificates manually turned out to be quite time consuming and inefficient. Then the absence of a verification system that can check the authenticity and ownership of certificates can provide opportunities for certificate forgery. So, it is very important to design and build a web-based electronic certificate application (e-certificate) that is able to generate certificates online and be able to verify the authenticity and ownership of the electronic certificates. This study uses a Research and Development (R&D) approach. This type of development method uses the waterfall approach. At the system design stage using the Unified Modeling Language (UML), and for the database using MySQL. The results of this study are web-based e-certificate applications that are designed successfully to support the process of generating and verifying the authenticity and ownership of electronic certificates online. Based on the results of testing the system with the black box method also shows that all the functionality of the e-certificate application that is designed to run very well and in accordance with user needs.